Estrutura da comunidade de rotíferos ao longo de um trecho sob a influência de barramentos de um rio Neotropical. - Mantovano, Tatiane (2015)
The construction of reservoirs requires considerable impact on freshwater ecosystems, because it changes all ecological aspects of the system lotic downstream of the dams. Due to the effects provided by numerous reservoirs located along the Paraná River, this study investigated the structure of rotifer community a stretch of river located between the reservoirs of Porto Primavera and Itaipu. The hypotheses tested were: (1) that community attributes (richness and abundance) will increase over the sampling points, as the river moves away from the dam of Porto Primavera and there is an increase in environmental variables related to trophic; (2) there will be a gradual replacement of species along the river, due to changes in environmental conditions of water, (3) and also that the rotifer community the last sampling point will be more influenced by variables related to trophic. Samples were taken to the subsurface of the pelagic region, with motor pump aid and plankton net of 68 micrometers. At the same time the sampling was to establish the physical and chemical variables of the water. 57 taxa belonging to 13 families were recorded. The largest number of taxa belonged to Brachionidae families, and Lecanidae Trichocercidae. The community composition showed different patterns on the dissimilarity between the studied points. In relation to wealth and abundance, there were no significant relationships with environmental variables trophic, since the Paraná River has a high volume of water, thereby minimizing the contributions as environmental variables from the tributaries. Despite the lack of significance for community attributes depending on the trophic variables for most sampling points was verified through redundancy analysis, significant relationship between these variables with the last sampling point, and the species of Brachionus calyciflorus and Keratella cochlearis, that is, a relationship between species that characterize these species environments with higher trophic levels.